The Need for Future Competencies of a Tourism Specialist from the Point of View of Employers - Bylaitė, Andželika; Jonaitienė, Ernesta; Kalinovienė, Vilma (Socialiniai tyrimai, 2022)
Employee competencies are considered to be the most important factor, which determines competitiveness among job seekers and an essential capital in most sectors of the economy. Today, due to the changing conditions in the labor market, the once acquired knowledge and abilities no longer meet the changed requirements, it is becoming important to develop generic and subject specific competencies. The article analyzes the generic and subject specific competencies of future specialists in the Lithuanian tourism sector, which are needed in the labor market of Lithuania from the point of view of employers. Therefore, using a semi-structured in-depth interview, a pilot professional activity field research was carried out in December 2020 – February 2021 in the economically strongest Lithuanian cities. The results of the research showed that due to the ongoing Covid-19 pandemic case, which is resonant and indefinite, the tourism market will never be the same again. It is observed that a person with a broader qualification (i.e. more competencies) easier integrates into the labour market. In this context, priority should be given to the ability of future specialists to be proactive and flexible, entrepreneurial and creative (to understand the specificities, future directions and trends of tourism and recreation services), to use information, smart and other technologies effectively. The specialist will not fear the competition of a professional who already has work experience in tourism sector.
Keywords: competencies; abilities; tourism and recreation; graduates; employers